Integrating Tongkonan and Christianity: A Strategy to Build Cultural and Spiritual Identity of Toraja Youth in the Midst of Urban Globalization - Jodih, Jodih; Risvan, Latupeirissa (Harati: Jurnal Pendidikan Kristen, 2025)
This study aims to examine the impact of globalization on the cultural and spiritual identity of Toraja youth, as well as the role of Tongkonan and the integration of Christian teachings in their lives amid urban life, particularly in Makassar. Globalization brings significant changes that affect the way people think, interact, and form their identities, including Toraja youth who are deeply connected to their cultural and traditional roots. The fast-paced urban life and the dominance of global culture have caused many Toraja youth to feel disconnected from their cultural heritage, leading to a crisis of identity. Meanwhile, the church, as a religious institution in Makassar, faces challenges in linking Christian teachings with Toraja cultural values, which are increasingly marginalized. Using the library research method, this study analyzes literature related to Toraja culture, Christian teachings, and the impact of globalization. The findings suggest the importance of integrating Toraja cultural values, such as the symbolism of Tongkonan, into Christian religious education so that Toraja youth can rediscover a more authentic and relevant sense of purpose amid the pressures of globalization. Religious education based on experience and reflection, and connecting local values with Christian teachings, can help form a strong and relevant spiritual identity for Toraja youth in the city.